TERRITORIAL LITERACY IN PUBLIC SCHOOLS: POETIC PRODUCTION AND THE CONSTRUCTION OF MEANING ABOUT LIVED SPACE - Yamaguchi, Andréa King de Abreu; Teske, Juciane Salgueiro de Mello; Reis, Mariana Moraes Camacho (Seven Editora, 2026)
This article analyzes the relationship between reading, territory, and the production of meaning about lived space, based on the pedagogical experience “Niterói in Verse,” developed with 4th-grade classes in a municipal public school. It is a qualitative research study, configured as an analytical experience report, with approaches to an interpretative case study. The corpus consists of students’ poetic productions, pedagogical records, and observations of teaching practice. The theoretical framework articulates Paulo Freire’s critical pedagogy, literacy studies, with emphasis on Magda Soares and Angela Kleiman, and critical geography, especially Milton Santos. The results indicate that poetic production favored the elaboration of meaning about the territory, highlighting different forms of relationship with space, such as sociability, daily practices, and perceptions of inequality. As a contribution, the study proposes the notion of territorial literacy, understood as the articulation between language, experience, and space in the production of socially situated meanings.